HUBUNGAN PEMBERIAN REWARD DENGAN MINAT BELAJAR SISWA MTs DARUL ILMI - Rahmarani Akmal Hia (PUSKAPAD, 2025)
This study aims to determine the relationship between reward giving and learning interest in eighth grade students of MTs Darul Ilmi. Based on the observation results, it was found that during the learning process, the teacher had given rewards but not optimally. This study was conducted using quantitative research methods. Based on the data and hypotheses, the reward variable has a relationship with the learning interest variable. This can be seen that the proposed hypothesis is accepted, namely with the value of